Pengaruh Teknologi Augmented Reality terhadap Pengalaman Pengguna dalam Desain Interior di Museum Wayang dan Fatahillah - Tuhfatul Habibah Hasibuan; Septiana Ningtyas; Jamah Sari; Taufiqurrochman; Harun Ar-Rasyid (Yayasan Pendidikan Mitra Mandiri Aceh (YPMMA), 2025)
The study aims to analyze how the application of Augmented Reality (AR) technology affects the user experience at the Wayang Museum and Fatahillah Museum. Augmented Reality technology is considered an innovation that can increase the interactivity, understanding, and satisfaction of museum visitors. With a mixed method approach, surveys, interviews, and observations were used to collect data in this study, resulting in 85% of respondents stating that AR technology increases their interactivity with museum artifacts and the average score for interactivity reached 4.3 on a scale of 5. Up to 90% of all respondents reported that AR features such as 3D animation, QR-Code, etc., allow them to understand culture and history better. In addition, there is a strong positive correlation between the use of AR technology and visitor satisfaction (r = 0.75, p < 0.01), 88% of participants expressed satisfaction with the AR-based exhibition experience. The application of this technology poses several challenges, including expensive development and maintenance, infrastructure limitations such as stable internet availability, and user devices that are not yet fully compatible. To address these barriers, it is recommended that infrastructure improvements, collaboration with technology partners, and staff training be implemented to increase understanding of how the introduction of AR technology can be used to enhance the museum visitor experience in a way that includes further integration of educational standards and interactive and enjoyable aesthetics to achieve greater potential for tourists and cultural education in general